الثقافة الصحية وعلاقتها بجودة الحياة لدى الطالب الجامعي - العدوالى,سارة; بليردوح,كوكب الزمان (University of Eloued جامعة الوادي, 2024)
Abstract: The study aimed to reveal the relationship between health behavior and quality of life among university students. The descriptive approach was relied upon, with the application of the health behavior scale designed by the researcher, the World Health Organization's short quality of life scale, to a sample of 100 students. After statistical analysis of the study hypotheses, the following results were reached: There is no statistically significant relationship between health behavior and quality of life among university students. The level of health behavior among sample members is high. The level of quality of life among university students The sample members are average. There are no differences in health behavior and quality of life among the sample according to gender. There are no statistically significant differences in the level of quality of life attributable to the specialization variable. هدفت الدراسة إلى الكشف عن العلاقة بين السلوك الصحي وجودة الحياة لدى الطالب الجامعي، تم الاعتماد على المنهج الوصفي مع تطبيق مقياس السلوك الصحي من تصميم الباحثة، مقياس جودة الحياة المختصر لمنظمة الصحة العالمية على عينة قوامها 100 طالب. بعد التحليل الإحصائي لفرضيات الدراسة تم التوصل لنتائج التالية: عدم وجود علاقة دالة إحصائيا بين السلوك الصحي وجودة الحياة لدى الطالب الجامعي، مستوى السلوك الصحي لدى أفراد العينة مرتفع، مستوى جودة الحياة لدى أفراد العينة متوسط، لا توجد فروق في السلوك الصحي وجودة الحياة لدى العينة باختلاف الجنس، لا توجد فروق ذات دلالة إحصائية في جودة الحياة تعزى إلى التخصص.
دراسة ميدانية بجامعة قسنطينة
Keywords: الثقافة الصحية; السلوك الصحي; Health culture; the behavior; healthy behaviour; quality of life; University student